Investigating thermal comfort of abandoned low cost houses in Sarawak based on construction materials - Ayagi, Kabiru Musa (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The housing industry in Malaysia is regarded as one of the major industries contributing to the economic and socio development of the country. Housing is a major concern for all people in every corner ofthe world as the wellbeing of a country is reflected in its people enjoying a certain standard of living. This research work aims at investigating and identifying the abandoned low cost houses in Sarawak, with special reference to a number of areas e.g. 1 Kuching, Kota Samarahan and Betong. Abandoned house can be define as property legally ./ unoccupied for at least six months and fulfil one of the number of the criteria, such as being in need of rehabilitation. The completed housing that has been abandoned may allow third parties to get rid of their waste materials in an illegal manner. In many situations an additional risk may be imposed by structural disintegration of the building over the years. This may lead to a direct danger that part of the structure could come down. Abandoned houses also do indeed have a negative impact on the value of houses in close proximity. According to our findings, there are a lot of factors contributed to low cost housing abandonment in Sarawak but for the purpose ofthis research we selected two ofthem i.e. materials and design. This research work was divided into two parts; the fll"St data collected were analysed using SPSS statistical software where the researcher found the respondents view about their residential area and the level of their comfort within the area. The second part of this research work was presentation of a study on different types of roofmg materials and construction using Energy Plus®, software simulation for thermal comfort in Sarawak Houses. Energy Plus® is a building simulation program for modelling building heating, cooling, lighting, ventilation and other energy flows. It is being developed by the government base on its predecessors, BLAST and DOE-2 and has undergone extensive testing to ensure that the internal models are reliable. Energy Plus® uses text based inputs and outputs which make it ii easier to analyse the data. Development of science and technology changes man's attitude towards life, which in turns was manifested his house design as well. Materials and tradition were became little significant as well as climatic design which almost neglected. The research work at the end give suggestions and recommendation to the Government and Developers the suitable Materials and design which will fulfil all the requirement of Sarawak climate for thermal comfort. Lightweight materials such as hollow block, veneer/ fibre-clad, cavity wall, lightweight concrete, zinc etc were recommended to be use for wall and roofing construction since they have low heat storing and there won't be much heat radiation towards the inner side of the building. Also materials such as concrete and bricks when use for construction, were suggested to be insulated from the outside since the absorbed large amount of heat, this heat is then released when the air becomes cooler.